STEAM-SDGs-Based Physics Learning Design on Renewable Energy Material to Improve Students' Literacy and Numeracy Skills - Riska Ajibudiarta; Nur Khoiri; Siti Patonah (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to design and evaluate a physics learning module based on the STEAM-SDGs approach on renewable energy material to improve students' literacy and numeracy skills. The background of this study is the low literacy achievements of Indonesian students in reading, mathematics, and science in international assessments such as PISA. To address this challenge, the development of innovative, contextually relevant teaching materials aligned with the United Nations' Sustainable Development Goals (SDGs) is necessary. This study employs the Research and Development (RD) method, utilizing the ADDIE development model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The developed product was validated by experts, tested in the classroom, and analyzed for its practicality and effectiveness. The results demonstrate that the developed teaching materials are valid, practical, and effective in enhancing students' understanding of renewable energy, while also significantly improving their literacy and numeracy skills. This research contributes to science education by integrating an interdisciplinary STEAM-based approach and sustainability-oriented content relevant to real-life contexts.